PENGARUH STRES KERJA, LINGKUNGAN KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Muhammad Alfian Rizky Pratama; Dwiarko Nugrohoseno (ITB AAS INDONESIA, 2022)
This research was conducted by researchers at PT XYZ, which is one of the companies engaged in the culinary industry in Indonesia. This research was conducted with the aim of knowing and proving the effect of work stress, work environment, and work discipline on employee performance. The population of the penitentiary system is about 1000 employees of PT XYZ, with a sample of 95 people responding with technical incident sampling. In this research, the technique for collecting data was obtained by distributing questionnaires through Google Form. Technical data analysis in research in this case descriptive analysis and inferential analysis with possible tools SmartPLS 3.2.9. Based on the tests in this study, it was found that the R Square Adjusted value was 0.800. The results of the hypothesis by this study state that, 1) work stress has a positive and significant effect of 0.417 on employee performance, 2) the work environment has a positive and significant effect of 0.400 on employee performance, 3) work discipline has a positive and significant effect of 0.157 on employee performance and 4) work stress, work environment and work discipline have a simultaneous effect on employee performance.